Religious Elit’s Communication and Strategy in Building Attitude of Tolerance in Plural Society in the Gunungsari West Lombok - Krisdiana, Putri; Misbahuddin (Universitas Muhammadiyah Yogyakarta, 2023)
This article discusses the strategy of the religious elite in building tolerance for a plural society in Gunungsari, West Lombok. The main problem studied is the strategy of Islamic and Hindu religious elites in internalizing and externalizing the value of religious tolerance in a plural society in Gunungsari. The writer uses three methods to get data about the main problem: observation, interview, and documentation. After conducting an analysis using qualitative methods, the authors found that religious elites had three strategies for instilling an attitude of tolerance: (1) Islamic religious elites instilled tolerance values in Muslim communities at religious events such as recitations at mosques. Likewise, the Hindu religious elite, their religious elite instills a value of tolerance at Piodalan events at temples, (2) The religious elite of Islam and Hinduism are the example, and role models for their followers and congregations, (3) In the event of a conflict, the Muslim and Hindu religious elites look for problem points by establishing communication to obtain a fair solution for both parties.